The Implementation of Field Experience Practice at Pangeran Antasari Kindergarten - Kharida Shaleha; Mita Kurniawati. M; Dwi Novita Sari (Outline Publisher, 2026)
Field Experience Practice is a program aimed at improving the quality of learning and field practice. The goal of the 2025 PPL program for Battuta University Early Childhood Education (PAUD) at Pangeran Antasari Kindergarten, located at Jl. Veteran No. 1060/19, Labuhan Deli District, Deli Serdang Regency, North Sumatra, was to provide kindergarten teachers with hands-on practice teaching in kindergarten. The PPL program encouraged Pangeran Antasari Kindergarten teachers to teach the Daily Activity Plan (RKH) and learning media. The program implemented programs such as toothbrushing, providing little doctors, decorating classrooms, organizing the school health center (UKS) and procuring first aid kits. The program also improved classroom and school administration, and procuring Educational Play Equipment (APE) to complement the toys and media used to support the learning process. Overall, the PPL program met its targets, as evidenced by the successful implementation of all planned programs. This was achieved thanks to the collaboration between students, the Pangeran Antasari Kindergarten community, the Field Supervisor, and other relevant parties who assisted in the implementation of the PPL program. The results of the program implementation showed that all activities.